The Determinants of Sovereign Sukuk Issuance from Organization of Islamic Cooperation Members - Charina Dwi Rivylina Nafisah; Agus Eko Sujianto; Nur Aini Latifah; Kiki Yunita Anjarsari; Achmad Budi Susetyo (Technium Social Sciences Journal, 2020)
The objective of this study is to analyze the factor of uncertain macroeconomics condition on the issuance of sovereign using four indicators, economic growth, inflation, exchange rate, and the money supply. The data is analyzed using the Fixed Effect Panel Regression Model. The finding of this study shows that partially, economic growth, exchange rate, and money supply have a positive and significant effect on the issuance of sovereign sukuk. However, only inflation shows a negative and significant effect on the issuance of sovereign sukuk. This means that inflation is inversely proportional to the issuance of sovereign sukuk. The increase in inflation will lower the issuance of sovereign sukuk and vice versa. The result of F-test finds that simultaneously economic growth, inflation, exchange rate, and money supply have a significant effect on the issuance of sovereign sukuk.